The Materiality of Street Art and Public Space Expression: A Literature Review on the Relationship Between Art, City, and Social Identity - Yustinus Ardhitya (International Journal Labs, 2026)
This research focuses on the materiality of street art and its contribution to shaping public spaces and representing the social identity of urban communities. In contemporary urban landscapes, street art practices reflect the complexity of social, political, and cultural dynamics, where material elements—such as paint, wall planes, and urban spatial textures—are not positioned solely as visual mediums but rather as entities that play an active role in shaping spatial meaning and experience. This study utilized a qualitative approach through the narrative literature review method, accompanied by thematic analysis of various scientific sources that examine the relationship between urban art, materiality, and social space. The findings show that street art has a dual function as both aesthetic and social practice; it presents a space for dialogue and resistance to symbolic domination in urban spatial planning while strengthening collective identity through participatory interaction between human subjects and material objects. The results confirm that materiality in street art contains agency that can reconfigure the relationship between art, space, and urban society. The contribution lies in integrating materiality theory, public space concepts, and participatory aesthetics to build a comprehensive understanding of street art as a social-material phenomenon. Thus, this study enriches theoretical discourse and practices in urban art studies while encouraging the formulation of urban policies that are more inclusive of participatory public art practices